Analysis of The Effect of Quiet Quitting and Competence on Employee Performance With Work Motivation As A Mediating Variable Among Generation Z Employees - Wulan Sulistya Ambarwati; Deden Sutisna M (International Journal of Science and Environment (IJSE), 2026)
The dynamics of the modern workplace have undergone significant changes along with the evolving expectations of employees regarding an ideal work environment. One of the emerging issues that has gained considerable attention in human resource management is the phenomenon of quiet quitting and employee competence, both of which may influence employee performance and work motivation. This study employs a field research method using a descriptive-verificative approach. The research was conducted at BPRS HIK Parahyangan involving Generation Z employees aged up to 30 years, with a total of 86 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4.0 software. The results reveal that quiet quitting does not have a significant effect on employee performance, but it has a significant effect on work motivation. The competence variable is found to have a significant effect on both employee performance and work motivation. However, the indirect effect analysis indicates that quiet quitting does not significantly affect employee performance through work motivation, and the indirect effect of competence on employee performance through work motivation is also not significant among Generation Z employees at BPRS HIK Parahyangan.